The use of intact proteins and purified amino acids in determining the methionine requirement in practical diets of pacific white shrimp, Litopenaeus vannamei - Stephanie F. Velasquez; D. Allen Davis; Alexis Weldon (Animal Feed Science and Technology, 2025)

Effects of Different Protein and Lipid Levels in Practical Diets for Yellowtail Snapper, Ocyurus chrysurus (Bloch, 1971) - Stephanie F. Velasquez; Leonardo Ibarra-Castro; Alexis Weldon; Donald Allen Davis (Journal of Marine Science and Engineering, 2024)
Yellowtail snapper Ocyurus chrysurus has great potential as a production fish in aquaculture, yet there is very limited information on its nutritional requirements. To establish baseline data, two trials were conducted to evaluate the effects of dietary protein and lipid levels in practical diets on growth and protein retention. The first trial, conducted over 14 weeks, used a series of diets with varying levels of protein (36%, 40%, and 44%) and lipids (6%, 10%, and 14%). The second trial, conducted for 10 weeks, used a series of diets with 36% protein and scaled lipid levels (7%, 10%, 13%, and 16%). Additionally, a commercial reference diet with 44% protein and 12% lipids was included. Growth performance and feed utilization parameters for Trial 1 indicated that the yellowtail snapper were able to effectively utilize practical diets containing 36% protein and 10% lipids, which produced the highest apparent net protein retention (ANPR; %) and survival. No significant differences were found in growth performance metrics, though there were numerical differences in final weight, weight gain, and survival. Similarly, in Trial 2, most growth metrics did not show significant differences. There were variations in weight gain, feed offered, and ANPR, with the highest performance observed in the fish given feed with 13% lipids. Based on the growth performance and ANPR values across these trials, we recommend 36% protein and dietary lipid levels of 7–13%, which are lower than the currently used commercial diets for marine finfish. The data gathered from the current study may be helpful for nutritionists in formulating feed to include more sustainable and cheaper feedstuffs and promote sustainable yellowtail snapper aquaculture production.

The efficacy of hydrolized feathermeal as a protein source in diets for juvenile catfish Ictalurus punctatus - Darci Carlos Fornari; Sidra Nazeer; Alexis Weldon; D. Allen Davis (Aquaculture, 2023)

Passive acoustic feeders as a tool to assess feed response and growth in shrimp pond production - João Reis; Aya S. Hussain; Alexis Weldon; Samuel Walsh; William Stites; Melanie Rhodes; D. Allen Davis (Aquaculture International, 2023)